Cooperative management reshapes seasonal nitrogen synchrony and surface-water nitrogen risk in pastoral regions - Tianyun Qi; Tianer Song; Mei Huang; Wenyin Wang; Binyu Luo; Shuai Qi; Cai’e Wang; Rong Rong; Lin Ma; Jianhui Xu; Tao Zhang; Yanfu Bai; et al. (Agriculture, Ecosystems & Environment, 2027)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

First report of Fusarium weifangense, F. puerense and F. asiaticum causing leaf spot disease on Morus alba L. in China - Mei Lei; Rong Xiao; Lixia Zhang; Yu Tian; Zhongrong Zheng; Zehui Zhao; Tingting Zhao; Zhu Li; Haixia Ding (Crop Protection, 2026)

Foraminiferal composition of the early Oligocene Globigerinid-rich limestone in the Baiyun Sag, Pearl River Mouth Basin, and its paleo-environmental significance - Guang-Rong Peng; Cui Shi; Xiao-Ping Li; Xin-Yu Liu; Le-Yi Xu; Kai Zhang; Qi-Mei Guo; Bao-Hua Li (Palaeoworld, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Bionic platelet membrane-coated rutin nanoparticles attenuate ulcerative colitis by suppressing platelet-mediated macrophage inflammation - Rong Zhang; Ruya Mei; Bingqing Liang; Xinyue Zhang; Tong Zhang; Jie Luo; Juhua Zhang; Qin Pan; Yuzhong Yan (Drug Delivery and Translational Research, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Biochar aging-driven cadmium release in paddy soils: Mechanistic insights into adsorption capacity loss and biochar feedstock-specific risks - Ze-ning Yu; Xiao-qing Zhang; Fei-mei Chen; Rong-liang Qiu; Kuan Zhou; Xin-xian Long (Journal of Environmental Sciences, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Trichoderma maomingense (Sordariomycetes, Hypocreaceae), a New Species Isolated From Bamboo in Guangdong Province, China - Dai‐Yan Huang; Qiu‐Rong Huang; Zhang‐Yong Dong; Mei Luo (New Zealand Journal of Botany, 2026)
Trichoderma species are widely distributed across various habitats worldwide and play significant roles in the biological control of plant diseases, plant growth promotion, and soil improvement. In this study, a novel Trichoderma species was isolated from dead culms of Bambusa cerosissima McClure in Maoming City, Guangdong Province, China. Based on morphological characteristics and multigene phylogenetic analyses of translation elongation factor 1 α ( tef1‐α ), nuclear internal transcribed spacer of rDNA region (ITS), and RNA polymerase second largest subunit ( rpb2 ) by both maximum likelihood (ML) and bayesian inference (BI) approaches, three isolates were identified as a new species within the Koningii‐clade, named Trichoderma maomingense sp. nov. The distinctions between this new species and its closely related taxa are discussed in detail.

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

From origin tracing, processing, to quality regulation: Molecular mechanism advances in medicinal foods research by integrating multi-omics tools - Jian-Hang Cai; Guan-Dong Fang; Yan Zhang; Jie Song; Jia-Yi Weng; Xue-Mei Ge; Issoufou Amadou; Xiang-Rong Cheng (Food Bioscience, 2026)

Construction of antibacterial-enhanced 2D ZnO@ZIF-8 nanocomposites based on synergistic antimicrobial mechanisms and application in maize long-term storage - Song-Yue Xu; Chao-Shuai Mei; Ke-Yu Zhou; Feng Xiao; Min Zhang; Qiong Wu; Yu-Rong Zhang; Dong-Dong Zhang (Food Chemistry, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

Wood-derived self-standing carbon electrodes for electrocatalysis: design, performance, and prospects - Liu-Liu Shen; Xinkun Li; Peiran Wu; Jiansong Wang; Hui Yu; Yipu Xu; Yuhang Wang; Gui-Rong Zhang; Donghai Mei (Chemical Engineering Journal, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

Trichoderma azadirachtae Ta3302: A novel biocontrol agent for banana Fusarium wilt and a promoter of plant growth - Mei Luo; Qiu-Rong Huang; Meng-Xuan Jia; Jin-Ying Zeng; En-Ru Dong; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The application of nutrients in enhancing drought tolerance of secretohalophyte Atriplex canescens in the desert regions of Northwest China - Jian-jun Kang; Wen-zhi Zhao; Zhi-bin He; Bing Liu; Rong Yang; Hai Zhou; Dong-Mei Zhang (Plant and Soil, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Megastigmane glycosides from Heterosmilax yunnanensis and their neuroprotective activity - Rong-Rong Du; Wen-Jie Qin; Xiu-Mei Duan; Xu Zhang; Ya-Nan Yang; Jian-Shuang Jiang; Xiang Yuan; Pei-Cheng Zhang (Phytochemistry, 2025)

A new sesquiterpene from endophytic fungus Colletotrichum sp. B-89 - Ke-tao Zhang; Bing Zhang; Zhi-pu Huang; Yu-xiao Xu; Xiao-rong Xu; Si-heng Li; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Evaluations of two ion temperature models in IRI-2020 based on the observations from ICON and COSMIC-2 IVM - Tingwei Han; Huijun Le; Shun-Rong Zhang; Vladimir Truhlik; Natalie Reeves; Angkita Hazarika; Yujin Cho; Mei-Yu Chen; Libo Liu; Yiding Chen; Ruilong Zhang (Advances in Space Research, 2025)

Spatiotemporal pattern of the East Asian monsoon hydroclimate during the 8.2 ka event inferred from a new speleothem multi-proxy record from SE China - Xiaomei Zhang; Haiwei Zhang; Rui Zhang; Jian Wang; Miaomiao Wang; Zeyuan Liang; Mei He; Rong Wei; Hai Cheng (Quaternary Science Reviews, 2025)

Recent advances in cold plasma technology for enhancing the safety and quality of meat and meat products: A comprehensive review - Changyan Zhang; Yulong Luo; Ziyao Deng; Rui Du; Mei Han; Junqin Wu; Wenxiu Zhao; Rong Guo; Yanru Hou; Songlei Wang (Food Research International, 2025)

A tumor-pH-responsive phthalocyanine as activatable type I photosensitizer for improved photodynamic immunotherapy - Ling Zhang; Rong-Bin Que; Ting-Ting Ke; Chao Wang; Wei Xie; Hong-Jie Sun; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang; Xingshu Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Phthalocyanine J-aggregate nanoparticles with enormous-redshifted and intense absorption: Potential structure-J-aggregation relationships and application in tumor-associated macrophages-targeted phototheranostics - Fengxiang Tang; Haodong Yu; Yanzong Huang; Xue Zhao; Zixuan Chen; Honglin Ma; Bi-Yuan Zheng; Mei-Rong Ke; Yongfan Zhang; Xingshu Li; Juyoung Yoon; Jian-Dong Huang (Chemical Engineering Journal, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Two-step synthesis of coconut shell biochar-based ternary composite to efficiently remove organic pollutants by photocatalytic degradation - Shipeng Zhang; Rong Wang; Jinhua Zhu; Xiaoyan Xie; Mei Luo; Hailong Peng; Yude Liu; Fei Feng; Ronghui Shi; Wang Yin (Journal of Environmental Chemical Engineering, 2024)

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

NiCoP cocatalyst modified g-C3N4 as ohmic junction photocatalyst for efficient degradation of tetracycline under visible light - Qinyi Gu; Chujun Feng; Jian Rong; Yuzhe Zhang; Xudong Zheng; Jinfeng Mei; Zhongyu Li; Song Xu (Environmental Research, 2024)

A new 1,4-benzoxazine derivative produced by endophytic Colletotrichum gloeosporioides B-142 - Bing Zhang; Zhi-pu Huang; Yu Si; Ke-tao Zhang; Xiao-rong Xu; Jian-hong Chen; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

A study of volatiles of young citrus fruits from four areas based on GC–MS and flash GC e-nose combined with multivariate algorithms - Qian Zhang; Rong Xue; Xi Mei; Lianlin Su; Wei Zhang; Yu Li; Jinguo Xu; Jing Mao; Chunqin Mao; Tulin Lu (Food Research International, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Ultrastable Dual-Matrix meditated CsPbBr3 composites with enhanced photoluminescence quantum yield and robust circular polarization luminescence - Pengfei Zhang; Rong Lu; Yang Chen; Huihui Wang; Mei Zhao; Lijie Zhang; Huile Jin; Shun Wang; Yihuang Chen; Shuang Pan (Chemical Engineering Journal, 2024)

Transpiration-mimicking wood-based microfluidic aluminum-air batteries: Green power sources for miniaturized applications - Wei Wang; Liu-Liu Shen; Peiran Wu; Hui Yu; Jiansong Wang; Yipu Xu; Xiangzun Dong; Xuanxuan Cui; Gui-Rong Zhang; Donghai Mei (Chemical Engineering Journal, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Geranylgeranylacetone, an inducer of heat shock protein 70, attenuates pulmonary fibrosis via inhibiting NF-κB/NOX4/ROS signalling pathway in vitro and in vivo - Rong Zhou; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Jiamin Liu; Songtai Yang; Wu Yao; Fang Zhou (Chemico-Biological Interactions, 2023)

GGA (geranylgeranylacetone) ameliorates bleomycin-induced lung inflammation and pulmonary fibrosis by inhibiting apoptosis and oxidative stress - Rong Zhou; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Jiamin Liu; Songtai Yang; Wu Yao; Fang Zhou (Molecular Biology Reports, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

A new δ-valerolactone produced by marine Streptomyces sp. YIM 13591 - Bing Zhang; Yu-ying Zhao; Zhi-pu Huang; Ke-tao Zhang; Xiao-rong Xu; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2023)

Molecular characterization and antimicrobial activity of NK-lysin in black scraper (Thamnaconus modestus) - Mei-Yi Liu; Yi-Rong Zhang; Jian-Hua Zhang; Liang Miao; Yun-Fei Dang; Chen-Jie Fei; Chang-Hong Li; Jiong Chen (Fish & Shellfish Immunology, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

Eudesmane−type sesquiterpenes from the rhizomes of Atractylodes macrocephala and their bioactivities - Hai-Xin Zhang; Jin-Guang Si; Jing-Rong Li; Meng Yu; Ling-Ling Qin; Chen-Xu Zhao; Tao Zhang; Zhong-Mei Zou (Phytochemistry, 2023)

Four new glycosides from Gerbera piloselloides - Ha Gao; Chen-Xu Zhao; Xin-Yao Luo; Jing-Rong Li; Xiao-Chuan Ye; Tao Zhang; Zhong-Mei Zou (Phytochemistry Letters, 2023)

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Tumor necrosis factor-α coordinates with transforming growth factor-β1 to induce epithelial-mesenchymal transition and migration via the NF-κB/NOX4 pathway in bronchial epithelial cells - Ke Li; Rong Zhou; Mingze Ma; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Fang Zhou (Molecular Biology Reports, 2022)

HucMSC-Ex alleviates inflammatory bowel disease via the lnc78583-mediated miR3202/HOXB13 pathway - Yuting Xu; Li Zhang; Dickson Kofi Wiredu Ocansey; Bo Wang; Yilin Hou; Rong Mei; Yongmin Yan; Xu Zhang; Zhaoyang Zhang; Fei Mao (Journal of Zhejiang University-SCIENCE B, 2022)

Quinolizidine alkaloids from the roots of Sophora flavescens - Jian-Chun Li; Zhi-Jun Zhang; Dan Liu; Ming-Yan Jiang; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2022)

Experimental Study on Mechanical Properties of Highly Swelling Soft Rocks in the Yanji Basin, Northern China - Rong Zhao; Xiong Wu; Ge Zhu; Xiaolei Wang; Aoshuang Mei; Xiao Zhang (Rock Mechanics and Rock Engineering, 2022)

Understanding the key factors determining rural domestic waste treatment behavior in China: a meta-analysis - Donghui Zheng; Jing Shen; Rong Li; Bei Jian; Jihong Zeng; Yongliang Mao; Xiaoning Zhang; Pradipta Halder; Mei Qu (Environmental Science and Pollution Research, 2022)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Neobacillus sedimentimangrovi sp. nov., a Thermophilic Bacterium Isolated from Mangrove Sediment - Rong Tang; Qi Zhang; Manik Prabhu Narsing Rao; Guo-Hong Liu; Jian-Mei Che; Min Lei; Bo Liu; Wen-Jun Li; Shun-Gui Zhou (Current Microbiology, 2021)

Antidepressant Effect of Paeoniflorin Is Through Inhibiting Pyroptosis CASP-11/GSDMD Pathway - Dan-Dan Tian; Min Wang; An Liu; Mei-Rong Gao; Chen Qiu; Wen Yu; Wen-Ju Wang; Kun Zhang; Le Yang; Yan-Yan Jia; Chang-Bin Yang; Yu-Mei Wu (Molecular Neurobiology, 2021)

Flavonoids as key bioactive components of Oxytropis falcata bunge, a traditional anti-inflammatory and analgesic Tibetan medicine - Mei-Rong Zhang; Kan Jiang; Jun-Li Yang; Yan-Ping Shi (Natural Product Research, 2020)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Sugar transporter genes in grass carp (Ctenopharyngodon idellus): molecular cloning, characterization, and expression in response to different stocking densities - Xiao Liang; Fengying Yan; Yu Gao; Mei Xiong; Haishan Wang; Kommaly Onxayvieng; Rong Tang; Li Li; Xi Zhang; Wei Chi; Marina Piria; Mirna Mrkonjić Fuka; et al. (Fish Physiology and Biochemistry, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Atorvastatin ameliorates depressive behaviors and neuroinflammatory in streptozotocin-induced diabetic mice - Zhang Hai-Na; Yu Xu-Ben; Tang Cong-Rong; Cao Yan-Cheng; Yang Fan; Xu Lei-Mei; Sun Ruo-Lan; Ye-Zi; Wang Ye-Xuan; Liang Jing (Psychopharmacology, 2020)

Developing stripe rust resistant wheat (Triticum aestivum L.) lines with gene pyramiding strategy and marker-assisted selection - Rong Liu; Jing Lu; Min Zhou; Shigang Zheng; Zehou Liu; Chihong Zhang; Mei Du; Minxiu Wang; Yunfang Li; Yu Wu; Lei Zhang (Genetic Resources and Crop Evolution, 2020)

Sky islands as foci for divergence of fig trees and their pollinators in southwest China - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Mei Liu; Qin Wang; Chuan Yuan; Lu‐Shui Zhang; Yan Chen (Molecular Ecology, 2020)
The dynamics of populations and their divergence over time have shaped current levels of biodiversity and in the case of the “sky islands” of mountainous southwest (SW) China have resulted in an area of exceptional botanical diversity. Ficus tikoua is a prostrate fig tree subendemic to the area that displays unique intraspecific diversity, producing figs typical of different pollination modes in different parts of its range. By combining climate models, genetic variation in populations of the tree's obligate fig wasp pollinators and distributions of the different plant phenotypes, we examined how this unusual situation may have developed. We identified three genetically distinct groups of a single Ceratosolen pollinator species that have largely parapatric distributions. The complex topography of the region contributed to genetic divergence among the pollinators by facilitating geographical isolation and providing refugia. Migration along elevations in response to climate oscillations further enhanced genetic differentiation of the three pollinator groups. Their distributions loosely correspond to the distributions of the functionally significant morphological differences in the male figs of their host plants, but postglacial expansion of one group has not been matched by spread of its associated plant phenotype, possibly due to a major river barrier. The results highlight how interplay between the complex topography of the “sky island” complex and climate change has shaped intraspecies differentiation and relationships between the plant and its pollinator. Similar processes may explain the exceptional botanical diversity of SW China.

Toxicity and metabolism of 3-bromopyruvate in Caenorhabditis elegans - Qiao-ling Gu; Yan Zhang; Xi-mei Fu; Zhao-lian Lu; Yao Yu; Gen Chen; Rong Ma; Wei Kou; Yong-mei Lan (Journal of Zhejiang University-SCIENCE B, 2020)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

METTL1 overexpression is correlated with poor prognosis and promotes hepatocellular carcinoma via PTEN - Qiu-Hong Tian; Mei-Fang Zhang; Jin-Sheng Zeng; Rong-Guang Luo; Yang Wen; Jun Chen; Liu-Gen Gan; Jian-Ping Xiong (Journal of Molecular Medicine, 2019)

Relationship between genetic variation in the α2A-adrenergic receptor and the cardiovascular effects of dexmedetomidine in the Chinese Han population - Shao-jun Zhu; Kui-rong Wang; Xiong-xin Zhang; Sheng-mei Zhu (Journal of Zhejiang University-SCIENCE B, 2019)

First report of isolation and complete genome of Vibrio rotiferianus strain SSVR1601 from cage‐cultured black rockfish ( Sebastes schlegelii ) associated with skin ulcer - Zheng Zhang; Yong‐xiang Yu; Yong Jiang; Yin‐geng Wang; Mei‐jie Liao; Xiao‐jun Rong; Kai Wang; Hao Zhang; Jing Chen (Journal of Fish Diseases, 2019)
Vibrio rotiferianus is an important marine pathogen of various aquatic organisms and can be found widely distributed in the marine environment. To further characterize this pathogen, the pathogenic properties and genome of V. rotiferianus SSVR1601 isolated from Sebastes schlegelii with skin ulcer were analysed. SSVR1601 was shown to be short rod‐shaped cell with a single polar flagellum. Different degrees of pathological changes in fish kidney, intestine, gills and liver were observed after SSVR1601 challenge. The SSVR1601 genome consists of two chromosomes and two plasmids with a total of 5,717,113 bp, 42.04%–44.93% GC content, 5,269 predicted CDSs, 134 tRNAs and 40 rRNAs. The common virulence factors including OMPs, haemolysin, flagellin, DNase, entF , algU , tcpI , acfB and rfaD were found in strain SSVR1601. Furthermore, factors responsible for iron uptake ( fur , fepC and ccmC ) and types II, IV and VI secretion systems were detected, which are likely responsible for the pathogenicity of SSVR1601. The antimicrobial resistance genes, bacA , tet34 and norM, were detected based on Antibiotic Resistance Genes Database. The phylogenetic analysis revealed SSVR1601 to be most closely related to V. rotiferianus strains CAIM577 and B64D1.

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

AMPKα inactivation destabilizes atherosclerotic plaque in streptozotocin-induced diabetic mice through AP-2α/miRNA-124 axis - Wen-Jing Liang; Sheng-Nan Zhou; Mei-Rong Shan; Xue-Qin Wang; Miao Zhang; Yuan Chen; Yun Zhang; Shuang-Xi Wang; Tao Guo (Journal of Molecular Medicine, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

Involvement of IL-17 in Secondary Brain Injury After a Traumatic Brain Injury in Rats - Tan Li; Yong-mei Zhang; Dong Han; Rong Hua; Bing-nan Guo; Shu-qun Hu; Xian-liang Yan; Tie Xu (NeuroMolecular Medicine, 2017)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Responses of soil nitrous oxide production and abundances and composition of associated microbial communities to nitrogen and water amendment - Qing Wang; Yu-Rong Liu; Cui-Jing Zhang; Li-Mei Zhang; Li-Li Han; Ju-Pei Shen; Ji-Zheng He (Biology and Fertility of Soils, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

Isolation, chemical characterization, and immunomodulatory activity of naturally acetylated hemicelluloses from bamboo shavings - Ju-qing Huang; Rui-ting Qi; Mei-rong Pang; Cong Liu; Guang-yu Li; Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Optimized culture medium for the production of flavonoids from Orostachys cartilaginea V.N. Boriss. callus cultures - Wan Bo Zhang; Xuan Chun Piao; Jin Rong Li; Ying Hua Jin; Mei Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2017)

Plasma Oxytocin and Arginine-Vasopressin Levels in Children with Autism Spectrum Disorder in China: Associations with Symptoms - Hong-Feng Zhang; Yu-Chuan Dai; Jing Wu; Mei-Xiang Jia; Ji-Shui Zhang; Xiao-Jing Shou; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Long-Acting Phospholipid Gel of Exenatide for Long-Term Therapy of Type II Diabetes - Mei Hu; Yu Zhang; Nanxi Xiang; Ying Zhong; Tao Gong; Zhi-Rong Zhang; Yao Fu (Pharmaceutical Research, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

The Inhibition Effect and Excessive Carbon Flux Resulting from Blocking Anthocyanin Biosynthesis Under Darkness in Begonia semperflorens - Kai Ming Zhang; Mei Li Guo; Dan He; Rong Hua Wu; Yong Hua Li (Journal of Plant Growth Regulation, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Role of immune tolerance in BALB/c mice with anaphylactic shock after Echinococcus granulosus infection - Qin Zhang; Jian-Rong Ye; Hai-Mei Ma; Jian-Jiang Wu; Tao Jiang; Hong Zheng (Immunologic Research, 2016)

Effect of long-term industrial waste effluent pollution on soil enzyme activities and bacterial community composition - Gangavarapu Subrahmanyam; Ju-Pei Shen; Yu-Rong Liu; Gattupalli Archana; Li-Mei Zhang (Environmental Monitoring and Assessment, 2016)

Floral Transcriptome Analyses of Four Paphiopedilum Orchids with Distinct Flowering Behaviors and Development of Simple Sequence Repeat Markers - Dong-Mei Li; Wei Wu; Di Zhang; Xiao-Rong Liu; Xiao-Fei Liu; Yi-Jian Lin (Plant Molecular Biology Reporter, 2015)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Determination of selected pharmaceuticals in tap water and drinking water treatment plant by high-performance liquid chromatography-triple quadrupole mass spectrometer in Beijing, China - Mei-Quan Cai; Rong Wang; Li Feng; Li-Qiu Zhang (Environmental Science and Pollution Research, 2015)

Rainfall and tillage impacts on soil erosion of sloping cropland with subtropical monsoon climate — A case study in hilly purple soil area, China - Jia-liang Tang; Xun-qiang Cheng; Bo Zhu; Mei-rong Gao; Tao Wang; Xi-feng Zhang; Pei Zhao; Xiang You (Journal of Mountain Science, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

The checkpoint 1 kinase inhibitor LY2603618 induces cell cycle arrest, DNA damage response and autophagy in cancer cells - Feng-Ze Wang; Hong-rong Fei; Ying-Jie Cui; Ying-Kun Sun; Zhao-Mei Li; Xue-Ying Wang; Xiao-Yi Yang; Ji-Guo Zhang; Bao-Liang Sun (Apoptosis, 2014)

Response of bacterial pdo1, nah, and C12O genes to aged soil PAH pollution in a coke factory area - Xue-Mei Han; Yu-Rong Liu; Yuan-Ming Zheng; Xiao-Xia Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Linkage between community diversity of sulfate-reducing microorganisms and methylmercury concentration in paddy soil - Yu-Rong Liu; Yuan-Ming Zheng; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Effects of Recombinant Human AMH on SCF Expression in Human Granulosa Cells - Rong Hu; Yan Lou; Fei-Miao Wang; Hui-Ming Ma; Xing Wu; Xiao-Mei Zhang; Juan Li; Ying-Pu Sun (Cell Biochemistry and Biophysics, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

Genome-Wide Phylogenetic Analysis of Stress-Activated Protein Kinase Genes in Rice (OsSAPKs) and Expression Profiling in Response to Xanthomonas oryzae pv. oryzicola Infection - Mei-Rong Xu; Li-Yu Huang; Fan Zhang; Ling-Hua Zhu; Yong-Li Zhou; Zhi-Kang Li (Plant Molecular Biology Reporter, 2013)

Induction of annexin by heavy metals and jasmonic acid in Zea mays - Mei-Liang Zhou; Xiong-Bang Yang; Qian Zhang; Ming Zhou; En-Ze Zhao; Yi-Xiong Tang; Xue-Mei Zhu; Ji-Rong Shao; Yan-Min Wu (Functional & Integrative Genomics, 2013)

Nicotianamine synthase gene family as central components in heavy metal and phytohormone response in maize - Mei-Liang Zhou; Lei-Peng Qi; Jun-Feng Pang; Qian Zhang; Zhi Lei; Yi-Xiong Tang; Xue-Mei Zhu; Ji-Rong Shao; Yan-Min Wu (Functional & Integrative Genomics, 2013)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

Halomonas nanhaiensis sp. nov., a halophilic bacterium isolated from a sediment sample from the South China Sea - Mei-Rong Long; Dao-Feng Zhang; Xin-Yi Yang; Xiao-Mei Zhang; Yong-Guang Zhang; Yuan-Ming Zhang; Honghui Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Advanced glycation end products promote proliferation of cardiac fibroblasts by upregulation of KCa3.1 channels - Li-Mei Zhao; Wei Zhang; Li-Ping Wang; Gui-Rong Li; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2012)

Aldehyde dehydrogenase protein superfamily in maize - Mei-Liang Zhou; Qian Zhang; Ming Zhou; Lei-Peng Qi; Xiong-Bang Yang; Kai-Xuan Zhang; Jun-Feng Pang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Functional & Integrative Genomics, 2012)

GWAS-linked GAK locus in Parkinson’s disease in Han Chinese and meta-analysis - Nan-Nan Li; Xue-Li Chang; Xue-Ye Mao; Jin-Hong Zhang; Dong-Mei Zhao; Eng-King Tan; Rong Peng (Human Genetics, 2012)

Effect of intensive multifactorial treatment on the intima-media thickness of large arteries in patients with new-onset type 2 diabetes mellitus - Xiao-hong Zhao; Zhe-rong Xu; Qin Zhang; Hai-feng Gu; Yun-mei Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Characterization of Prototheca zopfii Associated with Outbreak of Bovine Clinical Mastitis in Herd of Beijing, China - Jian Gao; Han-qi Zhang; Jian-zhong He; Yang-hua He; Shu-mei Li; Rong-guang Hou; Qiao-xing Wu; Yang Gao; Bo Han (Mycopathologia, 2012)

Blockade of acid-sensing ion channels protects articular chondrocytes from acid-induced apoptotic injury - Wei Hu; Fei-Hu Chen; Feng-Lai Yuan; Teng-Yue Zhang; Fan-Rong Wu; Chao Rong; Sheng Jiang; Jie Tang; Cheng-Cheng Zhang; Mei-Ying Lin (Inflammation Research, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Functional analysis of the HS185 regulatory element in the rice HSP70 promoter - Yu-Man Zhang; Yu-Mei Zheng; Na Xiao; Li-Na Wang; Yao Zhang; Rong-Xiang Fang; Xiao-Ying Chen (Molecular Biology Reports, 2012)

Overexpression of PGC-1β improves insulin sensitivity and mitochondrial function in 3T3-L1 adipocytes - Chun-Lin Gao; Guang-Ling Liu; Shi Liu; Xiao-Hui Chen; Chen-Bo Ji; Chun-Mei Zhang; Zheng-Kun Xia; Xi-rong Guo (Molecular and Cellular Biochemistry, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Tissue-specific distribution of uncoupling proteins in normal rats and rats with high-fat-diet-induced obesity - Chun-Mei Zhang; Ying Gu; Da-ni Qing; Jin-gai Zhu; Chun Zhu; Min Zhang; Xi-Rong Guo (Molecular Biology Reports, 2010)

Chewing substances with or without tobacco and risk of cardiovascular disease in Asia: a meta-analysis - Li-na Zhang; Yun-mei Yang; Zhe-rong Xu; Qi-feng Gui; Qin-qing Hu (Journal of Zhejiang University-SCIENCE B, 2010)

Ophiocerol, a novel macrocylic neolignan from the aquatic fungus Ophioceras dolichostomum YMF1.00988 - Jin-Yan Dong†; Le Wang†; Hong-Chuang Song; Li-Mei Wang; Kai-Ze Shen; Rong Sun; Guo-Hong Li; Lei Li; Ke-Qin Zhang (Natural Product Research, 2010)

Validity and reliability testing of the Chinese (mainland) version of the 39-item Parkinson’s Disease Questionnaire (PDQ-39) - Wei Luo; Xiao-hong Gui; Bo Wang; Wen-ying Zhang; Zhi-yuan Ouyang; Yi Guo; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2010)

Effects of mercury on the activity and community composition of soil ammonia oxidizers - Yu-Rong Liu; Yuan-Ming Zheng; Ju-Pei Shen; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2010)

Improvement of heat and drought photosynthetic tolerance in wheat by overaccumulation of glycinebetaine - Gui-Ping Wang; Zhen Hui; Feng Li; Mei-Rong Zhao; Jin Zhang; Wei Wang (Plant Biotechnology Reports, 2010)

Expression of a bee venom phospholipase A2 from Apis cerana cerana in the baculovirus-insect cell - Li-rong Shen; Mei-hui Ding; Li-wen Zhang; Wei-guang Zhang; Liang Liu; Duo Li (Journal of Zhejiang University-SCIENCE B, 2010)

Gene expression profiles in the prefrontal cortex of SHR rats by cDNA microarrays - Jie Qiu; Qin Hong; Rong-hua Chen; Mei-ling Tong; Min Zhang; Li Fei; Xiao-qin Pan; Mei Guo; Xi-rong Guo; Xia Chi (Molecular Biology Reports, 2010)

Identification of QTLs for yield and yield components of barley under different growth conditions - Da-wei Xue; Mei-xue Zhou; Xiao-qin Zhang; Song Chen; Kang Wei; Fan-rong Zeng; Ying Mao; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Microbial composition and diversity of an upland red soil under long-term fertilization treatments as revealed by culture-dependent and culture-independent approaches - Ji-Zheng He; Yong Zheng; Cheng-Rong Chen; Yuan-Qiu He; Li-Mei Zhang (Journal of Soils and Sediments, 2008)

Effect of siRNA on HSV-1 plaque formation and relative expression levels of UL39 mRNA - Ren Zhe; Zhang Mei-Ying; Kaio Kitazato; Nobuyuki Kobayash; Zhu Qin-Chang; Zhang Pei-Zhuo; Yang Zhi-Rong; Wang Yi-Fei (Archives of Virology, 2008)

An insulinoma with clinical and electroencephalographic features resembling complex partial seizures - Shuang Wang; Hai-tao Hu; Shu-qun Wen; Zhong-jin Wang; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2008)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Polymorphism of the mouse gene for the interleukin 10 receptor alpha chain (Il10ra) and its association with the autoimmune phenotype - Zan-Mei Qi; Jun Wang; Zheng-Rong Sun; Feng-Mao Ma; Qing-Rui Zhang; Sachiko Hirose; Yi Jiang (Immunogenetics, 2005)

Length Polymorphism of Thymidylate Synthase Regulatory Region in Chinese Populations and Evolution of the Novel Alleles - Huai-Rong Luo; Xue-Mei Lü; Yong-Gang Yao; Nobuyuki Horie; Keiichi Takeishi; Lynn B. Jorde; Ya-Ping Zhang (Biochemical Genetics, 2002)